Yoruba Oral Traditions and Communal Aesthetics in Olu Obafemi’s Selected Drama - Abe , Olanipekun Emmanuel (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
The history of African oral literature is located in oral tradition which is tied to communal living. African oral literature is a conglomerate of communal traditions that reflect African culture, experiences, and societies. Studies affirmed that Olu Obafemi’s ideological stance and investigation of the society is revolutionary and is geared towards seminal social change. This paper examines the aesthetics of oral literature, and explores the society through the prism of Olu Obafemi’s Naira Has No Gender and Scapegoats and Sacredcows by highlighting the different explication of oral forms portrayed by the dramatist. The paper reveals the writer's ideological disposition and vision as informed by his discursive engagement of larger issues through various oratory means. The placement of Nigerian songs and dance, proverbs, role-play technique, and audience participation are identified as signposts of Nigerian oral literature. The paper adopts Cultural Studies theory as its theoretical paradigm for its capacity to analyse and provides an assessment of the contributions that cultural practices and artifacts make to the society. This study reveals how African oral literature combines traditional and modern theatrical techniques to sustain communal living and cultural practices such as veneration, education, and moral instruction.